Types of Defamation Speech Acts on social media Instagram, Twitter, and Facebook in 2017-2019 - Hidayatillah, Adibatina; Subyantoro, Subyantoro; Haryadi, Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Nowadays, technological advances make it easier for us to access many things. Technology, especially the internet, can be easily accessed so that everyone can use it without exception. Social media, which is the outcome of technological advances, certainly has some negative impacts. One of the most common impacts, especially in Indonesia, is the defamation speech act. This study discusses the types of defamation speech acts on social media in the 2017-2019 period. It is qualitative descriptive research employing a theoretical approach namely forensic pragmatics. The data in this study were speeches suspected to contain elements of defamation on social media Instagram, Twitter, and Facebook in 2017-2019 and violated the ITE Law Article 27 paragraph (3) which has pragmatic power in the form of speech and the type of impoliteness strategy. The data in this study were collected utilizing screenshots of posts on social media Instagram, Twitter, and Facebook in 2017-2019 containing elements of defamation and violating the ITE Law Article 27 paragraph (3). This study applied the observation method. The equivalent method was used to analyze the data. The results of this study show that 43.34% of the defamation speech acts are in the form of assertive illocutionary speech act, 40% of expressive illocutionary speech act, 10% of directive illocutionary act, and 33.33% commissive and declarative illocutionary speech act.